FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Putri, Vidra Octavia Tjandra; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2024)
This study examines the effect of capital structure, company growth, company size, ownership, and dividend policy on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The use of the purposive sampling method, so as to get 27 selected companies that meet the criteria. Testing the data of this study using the Econometric Views (Eviews) 12.0 program. The results of the study show that capital structure has a positive and significant effect on company value, while company growth, company size, managerial ownership, and dividend policy do not affect company value.